The Application of Problem-Based Learning Improves the Learning Outcomes of Electric Motor Installation for Students of SMKN 1 Kulisusu - Rasyid, Muhammad; Algaus, Icong; Waode, Hamdi (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2023)
This classroom action research aims to improve the learning process by applying a problem-based learning model to improve learning outcomes for the Electric Motor Installation Protection System class XI TITL students of State Vocational High School 1 Kulisusu. This study uses two stages of the cycle. Cycle I students achieved learning outcomes of 45.7% (incomplete) and 54.8% (completed), with an average score of 68.34. Cycle II students achieved learning outcomes of 11.42% (incomplete) and 88.57% (completed), with an average value of 82.51. Applying this learning improves student outcomes in the second cycle stage, namely the achievement results of 88.57% of the total 35 students, with an average value of 82.51. Thus, a problem-based learning model can improve student learning outcomes in class XI TITL State Vocational High School 1 Kulisusu.